CS 173
Spring 2021

## Outline

Induction is a new proof outline, closely related to recursive definition in programming languages. It's used to prove that a property holds for all integers starting at some lowest value. (It can be adapted to prove a property for all integers, but we won't do that in this class.)

Suppose that our claim looks like:

Claim: For all integers n >= b, P(n).

In our proof by induction, we show two things:

• Base case:  P(b) is true
• Inductive step:  if P(n) is true for n=b, ..., k,   then P(k+1) is also true.

The base case gives us a starting point where the property P is known to hold. The inductive step gradually extends this guarantee to larger and larger integers.

When you're first starting out, it's helpful to divide the inductive step into two pieces: its hypothesis and the work required to prove its conclusion. So your proof by induction will look like this:

Proof: By induction on n.

Base case: [prove that P(b) is true]

Inductive hypothesis (IH): Suppose that P(n) is true for n=b, ..., k.

Rest of the inductive step:

... [work using the fact the IH is true] ...

So P(k+1).

It's also possible to make the inductive hypothesis cover values through k-1, and then the goal of the inductive step is to prove P(k). So that looks like:

Inductive hypothesis (IH): Suppose that P(n) is true for n=b, ..., k-1.

Rest of the inductive step:

... [work using the fact the IH is true] ...

So P(k).

These variations are equivalent and both are in common use. For some problems, one or the other may be slightly simpler to write.

## A Simple Example

Let's do a simple example to see how the method works.

Claim: for all integers $$n \ge 2$$,     $$\sum_{i=2}^n i 2^i = (n-1)2^{n+1}$$.

This claim gives a "closed form" for this summation, i.e. a formula that doesn't rely on a summation. I found this formula on the internet, so it's probably a bit mysterious. You might want to take a minute to put some small values of n into this formula, so that you have some basis for believing that it's correct.

Our induction variable is going to be n. For this simple example, n is the only possible choice, since i is the dummy variable for the summation. So our proof will start like this:

Proof: By induction on n.

This introductory line warns the reader that we're using an outline that isn't direct proof and tells him what the induction variable is. In more complex examples, it's not always obvious which variable we are going to use.

Our claim P(n) is $$\sum_{i=2}^n i 2^i = (n-1)2^{n+1}$$. Notice that P(n) needs to be a statement that's true or false. Or, said another way, it needs to contain a verb ("equals" in this example).

Now, notice that b = 2, because that's the smallest value for which we're claiming the formula works. To make the base case, we substitute b=2 for n in the claim. That is, the base case needs to show that $$\sum_{i=2}^n i 2^i = (n-1)2^{n+1}$$ at n=2, that is $$\sum_{i=2}^2 i 2^i = (2-1)2^{2+1}$$.

Proof: By induction on n.

Base case: At n = 2, $$\sum_{i=2}^n i 2^i = \sum_{i=2}^2 i 2^i = 2 \cdot 2^2 = 8$$ and $$(n-1)2^{n+1} = (2-1)2^{2+1} = 2^3 = 8$$. So $$\sum_{i=2}^n i 2^i = (n-1)2^{n+1}$$.

Now, substitute b=2 and P(n) into our outline to produce the inductive hypothesis and the goal of the inductive step. Notice that we substitute n=k+1 when making the goal. It's important to write out the goal of the inductive step. Once you start working on the middle of the inductive step, it's easy to forget exactly where you are headed. As you can see from this example, it's easy to imagine off-by-one errors.

Inductive hypothesis (IH): Suppose that $$\sum_{i=2}^n i 2^i = (n-1)2^{n+1}$$ is true for n= 2 , ..., k.

Rest of the inductive step:

... [work using the fact the IH is true] ...

So $$\sum_{i=2}^{k+1} i 2^i = k 2^{k+2}$$ which is what we needed to prove.

In this example, we only need to use part of the inductive hypothesis, i.e. that the claim is true at n=k. So let's make that explicit:

Inductive hypothesis (IH): Suppose that $$\sum_{i=2}^n i 2^i = (n-1)2^{n+1}$$ is true for n= 2 , ..., k.

Rest of the inductive step:
By the inductive hypothesis, $$\sum_{i=2}^k i 2^i = (k-1)2^{k+1}$$.

... [work using the fact the IH is true] ...

So $$\sum_{i=2}^{k+1} i 2^i = k 2^{k+2}$$ which is what we needed to prove.

In the inductive step, we know something about a short summation $$\sum_{i=2}^k i 2^i$$ and we'd like to work out the value of a longer summation $$\sum_{i=2}^{k+1} i 2^i$$. Our first task in writing the inductive step is to represent the big object in terms of one or more small objects. With a summation, we do this by removing the term for the largest index value.

Inductive hypothesis (IH): Suppose that $$\sum_{i=2}^n i 2^i = (n-1)2^{n+1}$$ is true for n= 2 , ..., k.

Rest of the inductive step:
By the inductive hypothesis, $$\sum_{i=2}^k i 2^i = (k-1)2^{k+1}$$.

$$\sum_{i=2}^{k+1} i 2^i = (k+1) 2^{k+1} + \sum_{i=2}^k i 2^i$$

... [work using the fact the IH is true] ...

So $$\sum_{i=2}^{k+1} i 2^i = k 2^{k+2}$$ which is what we needed to prove.

The inductive hypothesis tells us the value for the short summation, so let's substitute that into our equation:

Rest of the inductive step:
By the inductive hypothesis, $$\sum_{i=2}^k i 2^i = (k-1)2^{k+1}$$.

$$\sum_{i=2}^{k+1} i 2^i = (k+1) 2^{k+1} + \sum_{i=2}^k i 2^i = (k+1) 2^{k+1} + (k-1)2^{k+1}$$.

... [work using the fact the IH is true] ...

So $$\sum_{i=2}^{k+1} i 2^i = k 2^{k+2}$$ which is what we needed to prove.

Now, assess where you are by doing "compare and contrast" on the material before and after the gap. Looks like we have only one step of algebra to fill in to get our final proof.

Proof: By induction on n.

Base case: At n = 2, $$\sum_{i=2}^n i 2^i = \sum_{i=2}^2 i 2^i = 2 \cdot 2^2 = 8$$ and $$(n-1)2^{n+1} = (2-1)2^{2+1} = 2^3 = 8$$. So $$\sum_{i=2}^n i 2^i = (n-1)2^{n+1}$$.

Inductive hypothesis (IH): Suppose that $$\sum_{i=2}^n i 2^i = (n-1)2^{n+1}$$ is true for n= 2 , ..., k.

Rest of the inductive step:
By the inductive hypothesis, $$\sum_{i=2}^k i 2^i = (k-1)2^{k+1}$$.

$$\sum_{i=2}^{k+1} i 2^i = (k+1) 2^{k+1} + \sum_{i=2}^k i 2^i = (k+1) 2^{k+1} + (k-1)2^{k+1} = k 2^{k+2}$$.

So $$\sum_{i=2}^{k+1} i 2^i = k 2^{k+2}$$ which is what we needed to prove.

## Using it

Notice that we did the proof without having any good intuitions about why that closed form works. A great feature of induction is that it doesn't matter how we got our closed form. Perhaps this closed form just fell off the back of a truck and I found it beside the highway. Or perhaps I built a table of input and output values and made a guess. No matter where this formula came from, we can still use induction to prove that it's correct.